Effects of arsenite stress on growth and proteome of Klebsiella pneumoniae - Daware, Vandana; Kesavan, Suresh K.; Patil, Rajendra; Natu, Arvind; Kumar, Ameeta; Kulkarni, Mahesh J.; Gade, Wasudeo N. (Journal of Biotechnology, 2012)
In the present study an arsenite, As(III), tolerating bacterium, MR4, was isolated from Mulla River Pune, India, capable of reducing arsenate to arsenite and identified as Klebsiella pneumoniae (HQ857583). Comparative proteomic analysis using two-dimensional gel electrophoresis (2-DGE) and matrix assisted laser desorption ionization-time of flight-time of flight (MALDI-TOF/ TOF) was used to monitor the proteins undergoing changes in expression levels under 2.5 mM As(III) stress. The 2-DGE proteome map has shown that 60 proteins were differentially expressed under As(III) stress, of which 39 proteins were successfully identified with a MASCOT score greater than 70 (p < 0.05). Among the identified proteins, membrane transport/ binding proteins, porins, and amino acid metabolism enzymes were down-regulated while stress responsive proteins and antioxidant enzymes were up-regulated. Proteins involved in carbohydrate metabolism, particularly those in pentose phosphate pathway were also up-regulated while those involved in pyruvate metabolism were down-regulated. However, proteins involved in glycolysis and tricarboxylic acid cycle showed a mixed regulation response. These findings provide new insights into the probable mechanisms by which K. pneumoniae (HQ857583) could be adapting to As(III) stress. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: (2-DGE); Arsenite stress; Klebsiella pneumoniae; MALDI-TOF-TOF; Two dimensional gel electrophoresis

Enzymatic and non-enzymatic detoxification of reactive carbonyl compounds improves the oxidative stress tolerance in cucumber, tobacco and rice seedlings - Nareshkumar, Ambekar; Subbarao, Sindhu; Vennapusa, Amarnatha Reddy; Ashwin, Vargheese; Banarjee, Reema; Kulkarni, Mahesh J.; Ramu, Vemanna S.; Udayakumar, Makarla (Journal of Plant Growth Regulation, 2020)
Detoxification of reactive carbonyl compounds (RCC) is crucial to sustain cellular activity to improve plant growth and development. Seedling growth is highly affected by accumulation of RCC under stress. We report non-enzymatic, enzymatic mechanisms of detoxification of RCC in the cucumber, tobacco and rice seedling systems exposed to glucose, NaCl, methyl viologen (MV) induced oxidative stress. The cucumber seedlings exposed to carbonyl stress had higher levels of malondialdehyde (MDA), protein carbonyls (PCs) and advanced glycation end-product N-carboxymethyl-lysine (AGE-CML) that negatively affected the seedling growth. The overexpression of enzyme encoding aldo-keto reductase-1 (AKR1) in tobacco and rice showed detoxification of RCC, MDA and methylglyoxal (MG) with improved seedling growth under glucose, NaCl and MV-induced oxidative stress. Further, small molecules like acetylsalicylic acid (ASA), aminoguanidine (AG), carnosine (Car), curcumin (Cur) and pyridoxamine (PM) showed detoxification of RCC non-enzymatically and rescued the cucumber seedling growth from glucose, NaCl and MV-stress. In autotrophically grown rice seedlings these molecules substantially improved seedling growth under MV-induced oxidative stress. Seedlings treated with the small molecules sustained higher guaiacol peroxidase (GPX) enzyme activity signifying the role of small molecules in reducing carbonyl stress-induced protein inactivation and AGE-CML protein modifications. The results showed that besides enzymatic detoxification of RCC, the small molecules also could reduce cytotoxic effect of RCC under stress. The study demonstrates that small molecules are attractive compounds to improve the seedling growth under stress conditions.
Keywords: Oxidative stress; plant growth; Reactive carbonyl scavengers; Seed germination; small molecules

Elevated level of glycated KQTALVELVK peptide of albumin is associated with the risk of diabetic nephropathy - Chaurasiya, Arvindkumar H.; Jaiswal, Meera R.; Bayatigeri, Santhakumari; Kahar, Shweta; Tiwari, Shalbha; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2023)
Diabetic nephropathyis a leading cause of end-stagerenal disease.Hence, early detection of diabetic nephropathy is essential to mitigatethe disease burden. Microalbuminuria, the currently used diagnosticmarker of diabetic nephropathy, is not efficient in detecting it atan early stage. Therefore, we explored the utility of glycated humanserum albumin (HSA) peptides for risk prediction of diabetic nephropathy.Three glycation-sensitive HSA peptides, namely, FKDLG-EENFK,KQTAL-VELVK, and KVPQVST-PTLVEVSR, with deoxyfructosyllysine(DFL) modification were quantified by targeted mass spectrometry (MS)in a study population comprising healthy and type II diabetes subjectswith and without nephropathy. Mass spectrometry, receiver operatingcharacteristic (ROC) curve, and correlation analysis revealed thatthe DFL-modified KQTALVELVK peptide was better than other glycatedHSA peptides and HbA(1c) for identifying diabetic nephropathy.DFL-modified KQTALVELVK could be a potential marker for risk predictionof diabetic nephropathy.